Global TALES feasibility study: Personal narratives in 10-year-old children around the world - Westerveld, Marleen F; Lyons, Rena; Nelson, Nickola Wolf; Chen, Kai Mei; Claessen, Mary; Ferman, Sara; Fernandes, Fernanda Dreux M; Gillon, Gail; Kawar, Khaloob; Kraljević, Jelena Kuvač; Petinou, Kakia; Theodorou, Elena; et al. (My University, 2022)
Personal narratives make up more than half of children's conversations. The ability to share personal narratives helps build and maintain friendships, promotes physical and emotional wellbeing, supports classroom participation, and underpins academic success and vocational outcomes. Although personal narratives are a universal discourse genre, cross-cultural and cross-linguistic research into children's ability to share personal narratives is in its infancy. The current study addresses this gap in the research by developing the Global TALES protocol, a protocol comprising six scripted prompts for eliciting personal narratives in school-age children (excited, worried, annoyed, proud, problem situation, something important). We evaluated its feasibility with 249 ten-year-old children from 10 different countries, speaking 8 different languages, and analyzed researchers' views on the process of adapting the protocol for use in their own country/language. At group-level, the protocol elicited discourse samples from all children, although individual variability was evident, with most children providing responses to all six prompts. When investigating the topics of children's personal narratives in response to the prompts, we found that children from around the world share many commonalities regarding topics of conversation. Once again individual variability was high, indicating the protocol is effective in prompting children to share their past personal experiences without forcing them to focus on one particular topic. Feedback from the participating researchers on the use of the protocol in their own countries was generally positive, although several translation issues were noted. Based on our results, we now invite clinical researchers from around the world to join us in conducting further research into this important area of practice to obtain a better understanding of the development of personal narratives from children across different languages and cultures and to begin to establish local benchmarks of performance.
Keywords: Child; Communication; Emotions; Feasibility studies; Friends